1995
DOI: 10.1007/bf00045594
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal zonation of montane Quercus forests along two transects in Chirrip� National Park, Costa Rica

Abstract: Abiotic and vegetation data were collected along two altitudinal transects through mature montane Quereus forests on the Pacific and Atlantic slopes of Costa Rica's Chirrip6 Massif. Between 2000 and 3200 m asl twenty-four 0.05 ha forest plots were selected at altitudinal intervals of 100 m, and eight soil profiles were described at intervals of 200 m. A TWINSPAN classification aided in the determination of eight zonal forest communities on the basis of their floristic composition. They are grouped in two sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 45 publications
3
51
0
6
Order By: Relevance
“…The expected effects in the montane forests would be a decrease in the number of species and a reduction in the size of plants (Gentry, 1988;Sanchez, 2001;Wang et al, 2003). In principle the changes occurring with the increase in altitude, in particular a lower decomposition rate, should also reduce the rate of the regeneration process at higher altitudes, as compared with similar forests of the same age at lower altitudes (Kappelle et al, 1995;Pendry and Proctor, 1996;Sanchez, 2001). This, however, contradicts what was observed at Caucaia, where there were more forests at higher altitudes.…”
Section: Direct Influence Of Relief On Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The expected effects in the montane forests would be a decrease in the number of species and a reduction in the size of plants (Gentry, 1988;Sanchez, 2001;Wang et al, 2003). In principle the changes occurring with the increase in altitude, in particular a lower decomposition rate, should also reduce the rate of the regeneration process at higher altitudes, as compared with similar forests of the same age at lower altitudes (Kappelle et al, 1995;Pendry and Proctor, 1996;Sanchez, 2001). This, however, contradicts what was observed at Caucaia, where there were more forests at higher altitudes.…”
Section: Direct Influence Of Relief On Regenerationmentioning
confidence: 99%
“…In spite of the great diversity of approaches and analysis scales, several studies have shown that the richness and the composition of plant communities are influenced by relief characteristics such as slope orientation (Killingbeck and Wali, 1978), slope position (Oliveira Filho et al, 1994), altitude (Kappelle et al, 1995;Pendry and Proctor, 1996), and slope (Volpato, 1994). The heterogeneity of the topographic conditions can also affect the floristic composition (Swanson et al, 1988) as well as the richness and diversity of tree species (Everson and Boucher, 1998;Burnet et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, at each altitudinal interval of 100 m, temperatures were measured in top and sub-soils at intervals of 10-cm soil depth, using a digital Consort T 550 thermometer. Averages of hourly recordings (7 days) of air temperature and relative humidity were plotted in diurnal thermo-hygrograms following Ellenberg (1975), and presented in Kappelle et al (1995a).…”
Section: Climate Measurementsmentioning
confidence: 99%
“…and Atlantic slopes of Costa Rica's Talamancan mountain range (Kappelle et al 1989(Kappelle et al , 1991(Kappelle et al , 1995a(Kappelle et al , b, 2000Kappelle 1991Kappelle , 1996Kappelle and Zamora 1995;Oosterhoorn and Kappelle 2000;Chaps. 10, 15 and 17).…”
mentioning
confidence: 99%
See 1 more Smart Citation